2020
DOI: 10.1176/appi.ps.202000245
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Concerns Among Persons With Mental Illness

Abstract: The coronavirus disease (COVID-19) pandemic has been recognized as causing a wide variety of behavioral health problems. Society must mitigate this impact by recognizing that COVID-19 can trigger people's fears of exacerbating an existing mental illness. A survey about COVID-19 for people with mental illness was developed.Methods: Two hundred fourteen people responded to the survey, of whom 193 self-identified as living with a mental illness.Results: Almost all participants living with a mental illness (98%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 5 publications
4
49
1
4
Order By: Relevance
“…This suggest that we have to be careful to attribute worsening symptoms solely to this pandemic. In addition, our findings do not deny or neglect that people with existing anxiety and depression symptoms may have concerns about their mental illness worsening because of the COVID-19 pandemic [41].…”
Section: Discussioncontrasting
confidence: 55%
“…This suggest that we have to be careful to attribute worsening symptoms solely to this pandemic. In addition, our findings do not deny or neglect that people with existing anxiety and depression symptoms may have concerns about their mental illness worsening because of the COVID-19 pandemic [41].…”
Section: Discussioncontrasting
confidence: 55%
“…To our knowledge, there is no existing literature on COVID-19 pandemic among HCWs with pre-existing psychiatric diagnoses. COVID-19 poses a challenge to all HCWs, but an additional challenge to people with prior psychiatric illness due to disruptions to routines and mental health care leading to a potential for relapse or exacerbation of symptoms [14]. To address this important issue, we analyzed a group of frontline HCWs and found that the majority but not all of HCWs with pre-existing psychiatric conditions said the pandemic had affected them and increased their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There was a plea for more support. Understanding HCWs individual perception on the impact that COVID-19 had on their mental health, including feelings of isolation, can help us develop specific strategies to better alleviate their stress [14]. By learning various coping mechanisms or reaching out to mental health professionals before a time of acute stress, HCWs can be better equipped to acknowledge their condition and act on it [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations